RETRACTED: Battery technologies: exploring different types of batteries for energy storage - Rakhimov Ergashali; Khoshimov Diyorbek; Sultonov Shuxrat; Jamoldinov Fozilbek; Imyaminov Abdumannob; Omonov Bahrom (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001